Supplementation of grass hay with molasses in crossbred (Bos taurus X Bos indicus) non-lactating cows: effect of timing of molasses supplements on feed intake, digestion, DM degradation and rumen fermentation - Khalili, H.; Varvikko, T.; Osuji, P.O. (1993)
An experiment was carried out to evaluate the effects of molasses, given at different times, on feed intake, digestibility, degradation of hay dry matter (DM) and rumen pool fermentation. Four ruminally fistulated Friesian X Boran crossbred non-lactating cows were given a basal diet of grass hay ad libitum and noug cake. The other diets were supplemented with sugar cane molasses given at the same time or 2 hr. after a meal of the basal diet. The intake of hay was highest when molasses were given at the same time as the basal diet compared with the other molasses diets. Molasses increased the intake of total DM and crude protein. The apparent digestibility of DM was higher with molasses. The molasses diets had no significant effect on the degradation parameters of DM of grass hay. Molasses supplement decreased the mean concentration of ammonia N. The molar proportion of acetate was lower and propionate and butyrate higher with molasses diets.